Archeological and anthropological approaches to the ontology of the Dewil Valley landscapes (Palawan, Philippines) - Kowalczyk, Zuzanna (Folia Praehistorica Posnaniensia, 2022)
This paper is a discussion of the theoretical conceptualization of past landscapes and the limitations of archaeology in providing objectivistic interpretations. Analyzing a case study of the Dewil Valley landscape I will argue that the sciences about the past emerged based on the “Western” research paradigm. Therefore, local ontologies are often overlooked in archaeological narratives. In this article, I will present the ontologies of the indigenous Tagbanua people, contemporary beliefs related to the landscape, and theoretical approaches presented by researchers. I will argue that ontology can be complex and ambivalent, and that archaeological sources do not always indicate these dynamics.